Efektifitas Crossword Puzzle Therapy Terhadap Fungsi Kognitif Pada Lanjut Usia - Fajar Adhie Sulistyo; Sasni Triana Putri; Elpinaria Girsang; Bustomi Bustomi; Margaretha Rini; Deden Nurjaman (Universitas Malahayati, 2026)
ABSTRACT Data from the Indonesian Ministry of Health (2021) shows that the elderly population in Indonesia is projected to increase to 48.2 million people by 2035. According to WHO (2022), approximately 55 million older adults worldwide experience a decline in cognitive function, and around 7.7 million develop cognitive impairment each year. Various non-pharmacological interventions have been developed to maintain and improve cognitive function in the elderly, one of which is Crossword Puzzle Therapy (CPT). This therapy involves engaging in crossword puzzle activities that stimulate brain function, enhance memory, and train critical thinking skills. To determine the effectiveness of Crossword Puzzle Therapy on cognitive function in older adults. This study employed a pre-experimental design with a one-group pretest and posttest approach. The sample consisted of 16 respondents, with data collected through observation and administration of the MMSE test. The intervention group received CPT for 30–45 minutes, three times per week for four weeks. The hypothesis was tested using the Wilcoxon signed-rank test. There was a significant effect of Crossword Puzzle Therapy (CPT) on cognitive function in older adults, with a p-value of 0.000. CPT is effective in improving cognitive function in the elderly. This therapy can serve as a simple, low-cost, and accessible non-pharmacological intervention to help maintain the quality of life of older adults. Keywords: Crossword Puzzle Therapy, Elderly, MMSE. ABSTRAK Data Kemenkes RI tahun 2021 Populasi jumlah lansia di Indonesia pada tahun 2035 diperkirakan meningkat menjadi 48,2 juta orang. Data WHO (2022), ada sekitar 55 juta orang lansia mengalami penurunan kemampuan fungsi kognitif dan sekitar 7,7 juta lansia mengalami penurunan kemampuan kognitif per tahunnya. Berbagai intervensi non-farmakologis dikembangkan untuk mempertahankan dan meningkatkan fungsi kognitif pada lansia, salah satunya adalah Crossword Puzzle Therapy (CPT). Terapi ini melibatkan permainan teka-teki silang yang dapat merangsang kerja otak, meningkatkan daya ingat, serta melatih kemampuan berpikir kritis. Untuk mengetahui efektifitas Crossword Puzzle Therapy terhadap fungsi kognitif pada lanjut usia. Methods Desain penelitian ini pre-experimentaldengan pendekatan one group pretest and poststest design, Jumlah sampel 16 responden, teknik pengumpulan data menggunakan observasi, dan pengisian tes MMSE. Kelompok intervensi diberikan CPT selama 30–45 menit, 3 kali per minggu selama 4 minggu, dan uji hipotesis menggunakan uji wilcoxon signed rank test. Ada pengaruh Crossword Puzzle Therapy (CPT) dengan Fungsi Koqnitif pada Lansia, dengan nilai p-value 0.000 . CPT efektif dalam meningkatkan fungsi kognitif pada lansia. Terapi ini dapat menjadi intervensi non-farmakologis sederhana, murah, dan mudah dilakukan dalam upaya mempertahankan kualitas hidup lanjut usia. Keywords: Crossword Puzzle Therapy, Elderly, MMSE.